THE EFFECTIVENESS OF SARTANS AND ACE INHIBITORS IN ACUTE MYOCARDIAL INFARCTION ON THE BACKGROUND OF HYPERTENSION DISEASE - Talipov R.M., Nurmetov H.T. (Galaxy International Interdisciplinary Research Journal, 2023)
Mortality and disability of the population from coronary heart disease (CHD), in particular from acute myocardial infarction, remains the most urgent public health problem worldwide. The wide prevalence, severity of the course, high disability of patients indicate the importance of timely diagnosis and effective treatment of this disease [1,2,3]. However, despite the progress in diagnosis and treatment, acute myocardial infarction (AMI) retains the first place in the structure of mortality and disability in the population of economically developed countries, including our country. The level of lethality and disability in this disease is largely determined by the size of the lesion [4,5].